2015
DOI: 10.1021/acs.jafc.5b01086
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization and Anticancer Activity of Cell-Bound Exopolysaccharide from Lactobacillus helveticus MB2-1

Abstract: A novel cell-bound exopolysaccharide (c-EPS) was isolated from Lactobacillus helveticus MB2-1 by ultrasonic extraction, anion exchange, and gel filtration chromatography before being structurally characterized. The c-EPS is a heteropolysaccharide with an average molecular weight of 1.83 × 10(5) Da and is composed of glucose, mannose, galactose, rhamnose, and arabinose at a molar ratio of 3.12:1.01:1.00:0.18:0.16. Methylation analysis and nuclear magnetic resonance analysis revealed that the c-EPS is a linear g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(48 citation statements)
references
References 41 publications
4
41
0
3
Order By: Relevance
“…Similarly, heteropolymeric EPS production was shown in other L. helveticus strain. [21] These results clearly show that EPS production in koumiss and kurut LAB strains is an important characteristic that these strains harbour which can affect the technological properties of these products.…”
Section: Resultsmentioning
confidence: 67%
“…Similarly, heteropolymeric EPS production was shown in other L. helveticus strain. [21] These results clearly show that EPS production in koumiss and kurut LAB strains is an important characteristic that these strains harbour which can affect the technological properties of these products.…”
Section: Resultsmentioning
confidence: 67%
“…Different shapes and structures have been reported for different EPS. Li et al [ 38 ] showed that the EPS of Lactobacillus helveticus has rounded to spherical lumps of different sizes. Ahmed et al [ 37 ] found the reticulate shape for the ZW3 EPS.…”
Section: Resultsmentioning
confidence: 99%
“…2, most of the absorption bands could be assigned according to data obtained in previous studies. [50][51][52][53] The broad stretching intense peak at 3356 cm À1 indicated the presence of hydroxyl and amino groups, 54 the 2927 cm À1 region corresponded to the C-H stretching vibration. The band at 1649 cm À1 was the C]O stretching vibration of amide group.…”
Section: Extraction Purication and Physicochemical Properties Of H2mentioning
confidence: 99%